A GENERALIZED CONTRACTION PRINCIPLE IN MENGER SPACES USING A CONTROL FUNCTION - Dutta, P. N.; Choudhury, Binayak S. (Analysis in theory & applications, 2010)
In the present paper we use a control function to define a generalized contraction in Menger spaces and obtain a unique fixed point theorem. The work is in line with the research for developing probabilistic contractions with the help of control functions and related fixed point results. We have given an example to which our theorem is applicable. Some corollaries are also discussed.